2012
DOI: 10.1007/s00404-012-2243-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of educational software on self-efficacy of pregnant women to cope with labor: a randomized controlled trial

Abstract: The educational software program significantly increased self-efficacy of Iranian pregnant women to cope with labor. Despite lack of educational childbirth classes in Iran, the use of this method is recommended. However, to find whether this technique can be substituted for the educational classes, further studies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 33 publications
0
32
0
Order By: Relevance
“…Because outcomes of childbirth self-efficacy were not differentiated by race, however, of the researchers offer no insight into the role that race may or may not play in differences and/or disparities in childbirth self-efficacy. Childbirth self-efficacy research on women of racial majority in China (Gau et al, 2011; Hui Choi, 2012; Ip, Tang, & Goggins, 2009; Sun, 2010) and Iran (Vasegh Rahimparvar, Hamzehkhani, Geranmayeh, & Rahimi, 2012) has provided evidence that self-efficacy outcomes are similar comparing Caucasian and non-Caucasian women. It is important to note again, however, that we know very little about childbirth self-efficacy among women within racial minority communities.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because outcomes of childbirth self-efficacy were not differentiated by race, however, of the researchers offer no insight into the role that race may or may not play in differences and/or disparities in childbirth self-efficacy. Childbirth self-efficacy research on women of racial majority in China (Gau et al, 2011; Hui Choi, 2012; Ip, Tang, & Goggins, 2009; Sun, 2010) and Iran (Vasegh Rahimparvar, Hamzehkhani, Geranmayeh, & Rahimi, 2012) has provided evidence that self-efficacy outcomes are similar comparing Caucasian and non-Caucasian women. It is important to note again, however, that we know very little about childbirth self-efficacy among women within racial minority communities.…”
Section: Resultsmentioning
confidence: 99%
“…Only Vasegh Rahimparvar et al (2012) intentionally recruited women with lower incomes (Vasegh Rahimparvar et al, 2012). In the eight articles that did not clearly report income level, only Larsen et al (2001) and Slade et al (2000) did not report both income and education level (K.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[30] If pregnant woman thinks that she cannot control delivery, the consequential fear and anxiety makes her prefer CS in the absence of medical reasons. [31] Therefore, this study aimed to investigate factors associated with FOC and women's preference for elective CS.…”
Section: Significance Of the Studymentioning
confidence: 99%
“…Thus, this activity should be initiated during the antenatal period and be continued during labor to help women prepare both cognitively and emotionally for delivery. It has been shown that education offered on coping strategies for labor during the antenatal period increases self-efficacy, reduces pain and anxiety during the first and second stages of labor, and enhances the ability of prepartum women to manage their labor as well as their satisfaction with labor (Ferguson, Davis, & Browne, 2013;Ip, Tang, & Goggins, 2009;Malata, Hauck, Monterosso, & McCaul, 2007;Vasegh Rahimparvar, Hamzehkhani, Geranmayeh, & Rahimi, 2012). Women should be encouraged to make use of the information offered during labor.…”
Section: Introductionmentioning
confidence: 95%